2012
DOI: 10.2147/ijn.s29945
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of celastrol nanoparticles in a xenograft retinoblastoma tumor model

Abstract: Background: Celastrol, a Chinese herbal medicine, has shown antitumor activity against various tumor cell lines. However, the effect of celastrol on retinoblastoma has not yet been analyzed. Additionally, the poor water solubility of celastrol restricts further therapeutic applications. The goal of this study was to evaluate the effect of celastrol nanoparticles (CNPs) on r etinoblastoma and to investigate the potential mechanisms involved. Methods: Celastrol-loaded poly(ethylene glycol)-block-poly(ε-caprolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 38 publications
(45 reference statements)
1
24
0
Order By: Relevance
“…24 In the present study, we evaluated Tripterine, a triterpene compound, is known to inhibit proliferation of a variety of tumor cells, including U937 cells, human prostate cancer cell lines, HL-60 cells, and human melanoma cells. 25 In the present study, MTT assay results indicated that CT-NLC could enhance the antiproliferative effect of tripterine in PC-3 and RM-1 cells in a dose-dependent manner. In terms of IC 50 , both CT-NLC and T-NLC had a more remarkable inhibitory effect on the proliferation of PC-3 and RM-1 cells than did the tripterine suspension.…”
Section: Discussionsupporting
confidence: 58%
“…24 In the present study, we evaluated Tripterine, a triterpene compound, is known to inhibit proliferation of a variety of tumor cells, including U937 cells, human prostate cancer cell lines, HL-60 cells, and human melanoma cells. 25 In the present study, MTT assay results indicated that CT-NLC could enhance the antiproliferative effect of tripterine in PC-3 and RM-1 cells in a dose-dependent manner. In terms of IC 50 , both CT-NLC and T-NLC had a more remarkable inhibitory effect on the proliferation of PC-3 and RM-1 cells than did the tripterine suspension.…”
Section: Discussionsupporting
confidence: 58%
“…6, 7, 8, 9, 10, 11, 12, 13, 14, 15 In our previous report, we found that celastrol could induce different kinds of cell death including apoptosis, autophagy and paraptosis in cancer cells. 6 Importantly, our study using inhibitors of apoptosis, autophagy and paraptosis indicated that apoptosis was the type of cell death that mainly contributed to the cytotoxicity of celastrol.…”
mentioning
confidence: 90%
“…13,16 Recently, polymeric micelles have been used for ocular drug delivery to improve the drug release. 17,18 Drug-loaded polymeric micelles offer favorable biological properties, such as biocompatibility, biodegradability, mucoadhesiveness, nontoxicity, and controlled drug release. 19 Topical formulations of drug-loaded polymeric micelles hold significant promise for ophthalmic drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…30 PEG-PCL micelles have been widely used as drug-delivery carriers to improve the solubility of hydrophobic drugs. 17,31 In addition, PEI (Mw 1,800 Da) chains have been conjugated to classic PEG-PCL amphiphilic compounds to create superior cationic polymers due to their ability to develop molecular attraction forces via electrostatic interactions between the positively charged amino groups of PEI and the negatively charged sialic acid residues of mucin. There are also reports on the use of polymeric micelles prepared with mPEG-PCL-g-PEI copolymer for the codelivery of chemotherapy drugs and nucleic acid drugs into cancerous tumors.…”
mentioning
confidence: 99%